Antisense Oligonucleotide Reverses Leukodystrophy in Canavan Disease Mice. Issue 3 (22nd January 2020) - Hull, Vanessa; Wang, Yan; Burns, Travis; Zhang, Sheng; Sternbach, Sarah; McDonough, Jennifer; Guo, Fuzheng; Pleasure, David
Abstract : Marked elevation in the brain concentration of N‐acetyl‐L‐aspartate (NAA) is a characteristic feature of Canavan disease, a vacuolar leukodystrophy resulting from deficiency of the oligodendroglial NAA‐cleaving enzyme aspartoacylase. We now demonstrate that inhibiting NAA synthesis by intracisternal administration of a locked nucleic acid antisense oligonucleotide to young‐adult aspartoacylase‐deficient mice reverses their pre‐existing ataxia and diminishes cerebellar and thalamic vacuolation and Purkinje cell dendritic atrophy. Ann Neurol 2020;87:480–485